2015
DOI: 10.1016/j.jcrs.2014.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens power calculation for eyes with an axial length greater than 26.0 mm: Comparison of formulas and methods

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 12 publications
9
118
2
2
Order By: Relevance
“…Standard third-generation IOL calculation formulas, which use IOL constants, can lead to unexpected hyperopic IOL prediction errors in eyes with long axial length [17-22]. In this regard, Kane et al[21] reported that the mean prediction error of the IOLMaster in eyes with an axial length of ≥26 mm (version 5.4) was 0.21 dpt using the Haigis formula, –0.20 dpt using the Barrett Universal II, and 0.392 dpt or 0.370 dpt as the MedAE.…”
Section: Discussionmentioning
confidence: 99%
“…Standard third-generation IOL calculation formulas, which use IOL constants, can lead to unexpected hyperopic IOL prediction errors in eyes with long axial length [17-22]. In this regard, Kane et al[21] reported that the mean prediction error of the IOLMaster in eyes with an axial length of ≥26 mm (version 5.4) was 0.21 dpt using the Haigis formula, –0.20 dpt using the Barrett Universal II, and 0.392 dpt or 0.370 dpt as the MedAE.…”
Section: Discussionmentioning
confidence: 99%
“…22 Apart from technical difficulties, accurate refractive predictability of cataract surgery in highly myopic postvitrectomized eyes is challenging and often leads to unexpected postoperative hyperopia. 10 …”
Section: Discussionmentioning
confidence: 99%
“…9 Cataract surgery in highly myopic eyes can be complicated by zonular instability, extreme deepening of the anterior chamber (known as "lens-iris diaphragm retropulsion syndrome"), higher risk of postoperative retinal detachment, difficulties in predicting correct IOL power, and lower visual potential. [10][11][12] Theoretically, some of these challenges may be avoided by using FLACS, which helps to create a perfectly round anterior capsulotomy and softens the lens nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Adi Abulafia, et al 15 compared the predicted refractions calculated using standard formulae (Holladay 1, SRK/T, Hoffer Q and Haigis) with optical IOL constants, User Group for Laser Interference Biometry constants and concluded that the SRK/T, Hoffer Q, Haigis, Barrett Universal II, Holladay 2 and Olsen methods met the benchmark criteria of having a prediction error of ±0.5 D in at least 71.0% of eyes and ±1.0 D in 93.0% of eyes with positive power IOLs (>+6D ), whereas with low positive or negative powered IOLs Barrett Universal II formula and the Holladay 1 and Haigis formulae using the AL-adjusted method met those criteria.…”
Section: Age 43 To 69 Yearsmentioning
confidence: 99%